Protocol to operate a large-scale CO2 hydrogenation process for formic acid production - Bae, Jihoon; Park, Kwangho; Usosky, Denis; Jung, Kwang Deog; Lee, Ung; Kim, Changsoo (Cell Press, 2024)
Summary Formic acid is a viable product of CO2 utilization. Here, we present a protocol for designing and operating a pilot-scale formic acid production plant with a 10 kg/day capacity produced via CO2 hydrogenation. We describe the essential process specifications required for successful operation, including prevention of corrosion and formic acid decomposition. We then detail procedures for steady-state operation of the individual units. This protocol provides the necessary information for further scale-up and commercialization of the CO2 hydrogenation process. For complete details on the use and execution of this protocol, please refer to Kim et al.1